Group management and empowerment: lessons from development NGOs in Bangladesh - Md. , Moniruzzaman (SAGE, 2011)
Community development organisations employ group approach arguing that it strengthens the empowering capacity of local communities. Drawing on the experiences of two major NGOs in Bangladesh, this study argues that in community development greater attention usually is paid to the effects of ‘empowering’ inputs such as microcredit, while lesser importance is placed on the internal management of the group. This is a serious defect which may have direct negative effects on the empowering outcomes. This paper argues that paying greater attention to the internal management of the groups can make the group approach more effective in community development.